Leptin receptor defect with diabetes causes skeletal muscle atrophy in female obese Zucker rats where peculiar depots networked with mitochondrial damages. (2nd November 2021) - Gilloteaux, Jacques; Nicaise, Charles; Sprimont, Lindsay; Bissler, John; Finkelstein, Judith A; Payne, Warren R
ABSTRACT: Tibialis anterior muscles of 45-week-old female obese Zucker rats with defective leptin receptor and non-insulin dependent diabetes mellitus (NIDDM) showed a significative atrophy compared to lean muscles, based on histochemical-stained section's measurements in the sequence: oxidative slow twitch (SO, type I) < oxidative fast twitch (FOG, type IIa) < fast glycolytic (FG, type IIb). Both oxidative fiber's outskirts resembled 'ragged' fibers and, in these zones, ultrastructure revealed small clusters of endoplasm-like reticulum filled with unidentified electron contrasted compounds, contiguous and continuous with adjacent mitochondria envelope. The linings appeared crenated stabbed by circular patterns resembling those found of ceramides. The same fibers contained scattered degraded mitochondria that tethered electron contrasted droplets favoring larger depots while mitoptosis were widespread in FG fibers. Based on other interdisciplinary investigations on the lipid depots of diabetes 2 muscles made us to propose these accumulated contrasted contents to be made of peculiar lipids, including acyl-ceramides, as those were only found while diabetes 2 progresses in aging obese rats. These could interfere in NIDDM with mitochondrial oxidative energetic demands and muscle functions.